The blue dog project – The development of a dog bite prevention programme aimed at young children. (1st March 2011) - De Keuster, T; Meints, K; Butcher, R
Abstract : Dog bite injuries represent a serious health issue. A Belgian study indicated that every year 1% of the population suffers a dog bite requiring medical attention. Children are twice at risk than adults and severe injuries (neck and face) occur most frequently in young children. This age group usually gets bitten in their own home and by a dog that is familiar to them. Following a substantial bite, 55% of children suffer from post-traumatic stress disorder. According to research, children initiate most of the dog/child interactions that trigger the bite. There is no evidence to indicate any specific breed prevalence. One strategy is to educate young children, and their parents, to behave more safely with their own dog. The challenge is to find a method that is appropriate and develop it into an effective tool that can be scientifically validated. This was achieved by a team of professionals from multi-disciplines. The blue dog is an interactive CD that young children find fun to use while learning important lessons. Parent/teacher reinforcement is preferable, and a printed parent guide facilitates this. During play, the child is exposed to potential risk situations which involve two choices. The correct choice results in a favourable outcome and the story continues. An incorrect choice produces an unfavourable outcome. The story returns to the original decision point, allowing the child to alter their selection. The presentation will include videos of real life situations and the equivalent sections of the CD which are used to illustrate them.